Bisnis Online sebagai Pengembangan Ketahanan Sosial Ekonomi SeteBisnis Online sebagai Pengembangan Ketahanan Sosial Ekonomi Setelah Pandemi COVID-19 (Studi Kasus Bonassa Collection Gresik)lah Pandemi COVID-19 (Studi Kasus Bonassa Collection Gresik) - Kinanti, Anggreini Ratna (Jurnal Bisnis Indonesia, 2024)
During the pandemic, this had a significant impact on many areas, including the economic sector.One of the sectors affected is micro, small and medium enterprises (MSMEs). This situation requiresMSMEs, including the fashion industry, to be able to adapt and recover after the Covid-19pandemic.To achieve economic and social recovery in society, adaptive behavior must be implementedso that product production and marketing can run well. This service aims to grow the operations ofMSME owners by increasing economic and social resilience. The Bonassa UMKM collection waschosen because its location is a well-developed center for production and sales of Muslim fashion.The result of this service activity is an increase in online business capacity as well as the economicand social resilience of the Bonassa Collection fashion.Keywords: Socioeconomic Resilience; UMKM; Online Business